Hubungan Pengetahuan Teknik Mengejan Pada Ibu Bersalin Dengan Kejadian Ruptur Perineum Di PMB A. Aritonang Kec. Paranginan Kab. Humbang Hasundutan Tahun 2023 - Khairunnisa Situmorang; Defiana Nainggolan; Humaida Hanim (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
One of the causes of bleeding is due to perineal rupture. This type of research is an analytic survey with a cross-sectional research design. The number of samples used was 34 people obtained by using the total sampling technique. Data analysis technique using chi square. The results obtained in this study were that most of the mothers who had good knowledge of the absence of Perineal Rupture were 18 people (52.9%), and most of the mothers who had poor knowledge of the occurrence of Perineal Rupture were 7 people ( 20.6%). Based on the results of the chi square test, there is a relationship between Knowledge of Straining Techniques in Maternal Birth and Perineal Rupture with a P value = 0.014 <0.05. There is a relationship between Knowledge of Straining Techniques in Maternity Mothers with Perineal Rupture. It is recommended that mothers in labor seek more information to increase their knowledge, especially about pushing techniques to avoid perineal rupture through media on the internet, health workers, and so on.